Household financial management with personality factors and locus of control through mental budgeting - Eka Rosalina; Wiwik Andriani; Elfitri Santi; Asratul Rahmi (International Ecsis Association, 2022)
Personality and locus of control cannot be separated from within a person given the high consumption growth and supported by a luxurious lifestyle compared to a relatively low income. This study aims to determine the influence of personality and locus of control on the management of household finance through mental budgeting. This research was conducted through a questionnaire survey which was distributed to housewives with an age range of 20-50 years, SMA/SMK, not working, and not earning. The sample of this study was 140 samples using convenience sampling technique, then continued with hypothesis testing using path analysis on the SEM (Structural Equation Modeling) model using STATA 16 software. The results of this study stated that motivation and locus of control variables directly affect management of household finance. Meanwhile, the commitment variable does not directly affect the management of household finance. The mental budgeting variable as an intervening variable does not directly affect the management of household finance. Mental budgeting cannot mediate the relationship between motivation, commitment and locus of control with management of household finance.